INFANTILE LACTASE DEFICIENCY AND DIETARY HABITS. CLIUNICAL CASES - M. G. Ipatova; M. I. Dubrovskaya; T. I. Korneva; E. K. Kurgasheva; Yu. G Mukhina (Вопросы современной педиатрии)
This article contains analysis of modern data upon infantile lactase deficiency, diagnostics and clinical presentation. Special attention is paid to the disease treatment analysis and its dietary correction. We present clinical variants of the disorder.